ANALYSIS OF THE INFLUENCE OF THE HUMAN DEVELOPMENT INDEX (HDI) AND UNEMPLOYMENT RATE OPEN (TPT) AGAINST POVERTY IN NORTH SUMATRA PROVINCE - Mentari Syahputri Purba; Kezia Br Aritonang; Sena Samosir; Roni Sianturi (Universitas Negeri Medan, 2024)
Poverty is a fundamental problem for every country, especially for developing countries. Theinability to meet basic needs in all aspects of life where people cannot maximize the functionof the wealth they have. There is an increase in the number of poor people both from aglobal scope in Indonesia, especially also in North Sumatra Province. The purpose of thisstudy was to determine and analyze the effect of the Human Development Index (HDI) andthe Open Unemployment Rate (OUR) in North Sumatra Province. This study uses secondarydata from BPS Province for the observation year 2017- 2022. The research method used isthe panel data regression method with the help of the Eviews12 application. The results ofthis study are a) the Human Development Index (HDI) has a negative and significant effect onpoverty in North Sumatra Province, b) the Open Unemployment Rate (OUR) has nosignificant effect on poverty in North Sumatra Province, c) simultaneously the HumanDevelopment Index (HDI) and the Open Unemployment Rate (OUR) have a significant effecton poverty in North Sumatra Province. The results of this study also show that thecontribution of the Human Development Index (HDI) and the Open Unemployment Rate(OUR) variables to poverty is 53.21 percent.